The Clinical Significance and Potential Role of C-Reactive Protein in Chronic Inflammatory and Neurodegenerative Diseases - Luan, Ying-yi; Yao, Yong-ming (Frontiers in Immunology, 2018)
C-reactive protein (CRP) is an acute-phase protein synthesized by hepatocytes in response to pro-inflammatory cytokines and the action of interleukin-6 on the gene responsible for the transcription of CRP during inflammatory/infectious processes. CRP exists in conformationally distinct forms such as the native pentameric CRP (pCRP) and modified/monomeric CRP (mCRP) and may bind to distinct receptors and lipid rafts and exhibit different functional properties. It is known as a biomarker of acute inflammation, and many large-scale prospective studies demonstrate that CRP is both a predictor and participant in the development of cardiovascular diseases and known to be associated with chronic inflammation. In this review, we summarize and critically discuss the different functions and clinical significance of CRP in chronic inflammation and neurodegeneration. In addition, we highlight the advances in these areas that may be translated into promising measures for the diagnosis and treatment of inflammatory diseases.